Improving Bisphosphonate Infusion Monitoring at Haematology Medical Day Unit. Issue 1 (31st March 2017) - Ong, Michal Wen Sheue; Jones, Lydia
Abstract : This project was started after an incident of bisphosphonate-induced hypocalcaemia in September 2015. As part of management of lytic bone lesions in patients with multiple myeloma were given either Zoledronic Acid or Pamidronate Disodium at our Haematology Day Unit. According to the British National Formulary (BNF), it is necessary to correct disturbances of calcium metabolism (e.g. vitamin D deficiency, hypocalcaemia) and consider dental check-ups before starting bisphosphonate infusion due to the risk of osteonecrosis of the jaw. There was no formal checklist in place for all patients prior to starting bisphosphonate infusion. The aim of this quality improvement project was (1) to avoid preventable bisphosphonate induced adverse effects, (2) to improve safety of bisphosphonate prescribing and administration and (3) to increase patient's awareness of needing regular dental checks. Interventions were modified over multiple Plan-Do-Study-Act (PDSA) improvement cycles to improve bisphosphonate infusion monitoring and patient safety.There was an overall improvement in ensuring safety checks were done prior to administration of bisphosphonate infusion compared to baseline measurements. At baseline, 36% (n=9) of patients had a dental check within the last 6 months; after PDSA cycle 3, there was an improvement of up to 69% (n=11). All patients had renal function and bone profile checked prior to infusion from throughout the study. It was all recorded in the blood results section of the checklist with no missing data. We found that 32% (n=8) of patients had never had 25-OHD at baseline. After PDSA cycle 3, all patients had 25-OHD checked at some point.